Staphylococcus spp. in periodontal pockets from a group of patients attending a dental center in the Municipality of San Diego, Carabobo State - Davide Mobili-Rocaro; Daniela Falcón; Mariangel Rodríguez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2017)
Some unusual microorganisms have been isolated from samples  of  patients  with  oral  cavity  periodontal  disease.  The  objective  of  this  research  was  to  determine  the  frequency of  Staphylococcus  spp.  in  periodontal  pockets  based  on  the  epidemiological  characteristics   of patients attending a dental center  in  the  municipality  of  San  Diego,  Carabobo  state.  Samples from periodontal pockets  of  50  patients  attending  the  dental  center  were studied.  The isolated strains were identified by biochemical tests and finally the profile of antimicrobial susceptibility was determined. It was found that the frequency of patients with Staphylococcus spp. was 32%, 16 patients. Staphylococcus Coagulase Negative (SCN) was isolated in 10 patients, followed by S. aureus in 6. Regarding to antimicrobial susceptibility profile, it was determined that of the 6 isolated strains of Staphylococcus aureus, 2 proved to be Methicillin-resistant. The presence of Staphylococcus spp. in periodontal pockets is low frequency; however in this study, the presence of said microorganism was determined in 32% of the patients studied, which means that these patients are more colonized than what is believed.